PRODUKSI UMKM SELAMA PANDEMI DI DESA UJUNG JAYA KABUPATEN SUMEDANG - Adelse Prima Mulya; Siti Mutia Kosassy; Andry Pratama; Handika Aditama (Jurnal Public Administration, Business and Rural Development Planning, 2021)
The pandemic has hit Indonesia for more than two years, not only in the health sector, the education sector, the pandemic has also greatly impacted the economic sector, especially small economic actors, micro, small and medium enterprises (MSMEs). MSMEs are heavily affected, especially in the production process. This study aims to see an overview of MSME production during the pandemic in Ujung Jaya Village, Sumedang Regency. This research is a descriptive study, to see a description of the production of MSMEs in Ujung Jaya Village during the pandemic period which was carried out in June - July 2021. The population in the study of all community groups who had MSMEs registered with the Cooperatives were 83 MSMEs. The picture of MSME production is measured by conducting interviews with the owners of each MSME. The results of this study indicate that a decrease in the number of MSME production during the Covid-19 pandemic, including rice stalls/food stalls experiencing a 40% decrease in production, a 54.2% decrease in the production of pastries/wet cakes, an 11.1% decrease in vegetable cultivation or the like. and a 70% reduction in artisan production during the pandemic. For this reason, things that need to be considered for further improvement include marketing with digital patterns both in the marketplace and on social media, in order to increase production and sales again.